Communicative Teaching of a Foreign Language and its Practical Significance - Kambarova Dilorom Yusupovna (Journal of Innovation in Education and Social Research, 2024)
Recently, in the field of learning foreign languages, the concept of “communication” and “communicative approach” in teaching has become especially popular. In foreign methodological literature, this concept is referred to as Communicative language teaching (CLT) or Communicative approach. In a broad sense, these terms denote an approach to teaching a foreign language in which communication, the process of interaction with a speech partner, is both a means and a goal of learning. In this article, we will consider the issues of communicative learning of a foreign language